Production of functional CD19 CAR T cells under hypoxic manufacturing conditions - Micallef Nilsson, Isabella; Poiret, Thomas; Ryu, Jinhye; Mohammadpour, Mohammadali; Henriksson, Johan; Österborg, Anders; Mattsson, Jonas; Schurich, Anna; Magalhaes, Isabelle (Frontiers in Immunology, 2025)
IntroductionChronic lymphocytic leukemia (CLL) has proven difficult to treat with chimeric antigen receptor (CAR) T cell therapy. CLL cells can negatively alter T cell fitness and induce a pseudohypoxic state. We hypothesized that production of CAR T cells under restricted oxygen conditions resembling physiological oxygen levels that can be encountered in tissues (i.e. 2% O2) could promote outgrowth of hypoxia-tolerant CAR T cells.MethodsWe performed in vitro phenotypic and functional assessments of CD19-directed CAR T cells produced in either 21% (NorCAR) or 2% (HypCAR) O2 derived from healthy donors (HDs) or patients with CLL. ResultsProduction of HD-derived CAR T cells in 2% O2 promoted the enrichment of a naïve-like subset. HypCAR and NorCAR cells were functionally distinct; CD4+ HypCAR cells produced more IL-2 and tumor necrosis factor than CD4+ NorCAR cells. Production in 2% O2 was not detrimental to viability or proliferation upon cognate antigen-stimulation and led to increased activation. After chronic stimulation in hypoxia, HypCAR-product remained enriched in naïve-like cells, and demonstrated cytotoxic and cytokine production capacity. In CAR T cells derived from patients with CLL, NorCAR and HypCAR subsets were functionally and phenotypically comparable, but displayed different mitochondrial metabolism. DiscussionWe demonstrated that production in 2% O2 is not detrimental, confers subtle but lasting functional and phenotypic changes in CAR T cells warranting further research on the impact of hypoxic production on CAR T cell functionality in hypoxic tumor microenvironments.